Ni(II)-catalyzed intramolecular C-H/C-H oxidative coupling: an efficient route to functionalized cycloindolones and indenoindolones - Ankade, Shidheshwar B.; Samal, Pragnya Paramita; Soni, Vineeta; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (ACS Catalysis, 2021)
Nickel(II)-catalyzed intramolecular C(sp(2))-H/C(sp(3))-H and C(sp(2))-H/C(sp(2))-H oxidative couplings in indoles are achieved via chelation assistance. These reactions provide access to biologically relevant five- and six-membered substituted cyclopentaindolones, carbazolones, and indenoindolones in high yields and good chemoselectivity employing an air-stable and defined nickel catalyst, (bpy)Ni(OAc)(2). The oxidative cyclizations proceeded either through a six-membered or an unconventional seven-membered nickelacycle. An extensive mechanistic investigation by experiments and theoretical calculations revealed a facile indole's C(2)-H nickelation and a rate-limiting reductive elimination process. This intramolecular oxidative cyclization operates via a probable Ni(II)/Ni(III) pathway involving single-electron oxidation of nickel without the participation of a carbon-based radical.
Keywords: C-H activation; cycloindolones; indenoindolones; indoles; Mechanism; Nickel; oxidative coupling